Kasus Korupsi Timah Rp 271 Triliun: Alasan Kekuasaan, Kesempatan, dan Lemahnya Konstitusi - Tsalsabillah Rokhmah Utami; Sri Isnani Setiyaningsih (Institut Teknologi dan Bisnis Semarang, 2024)
Corruption is a serious problem in Indonesia, affecting economic growth, political stability and public trust in the government. This article discusses three main factors causing corruption in Indonesia: the desire to gain power, the availability of opportunities for corruption, and the weakness of the constitutional system to ensure accountability and transparency. This study shows how political power, weak control and supervision, as well as unclear constitutional provisions and weak understanding of Pancasila have created an environment that supports corrupt practices. This analysis also highlights the importance of constitutional reform and strengthening supervisory institutions to combat corruption and build a more transparent and accountable government in Indonesia.